Smoking and coronary artery disease risk in patients with diabetes: A Mendelian randomization study - Chen, Songzan; Yang, Fangkun; Xu, Tian; Wang, Yao; Zhang, Kaijie; Fu, Guosheng; Zhang, Wenbin (Frontiers in Immunology, 2023)
Abstract Background: Previous observational studies have shown an association between smoking and coronary artery disease (CAD) in patients with diabetes. Whether this association reflects causality remains unestablished. This study aimed to explore the causal effect of smoking on CAD in patients with diabetes. Methods: Genetic signatures for smoking were extracted from a large genome-wide association study (GWAS), consisted of up to 1.2 million participants. Four smoking phenotypes were included: smoking initiation, cigarettes per day, age at initiation of regular smoking, and smoking cessation. Genetic associations with CAD in patients with diabetes were extracted from another GWAS, which included 15,666 participants (3,968 CAD cases and 11,696 controls). The analyses were performed using the univariable and multivariable Mendelian randomization (MR) method. Results: MR analysis revealed that smoking initiation was positively related to CAD risk in patients with diabetes (OR = 1.373, 95% CI = 1.170 – 1.611, P = 9.96 × 10-5), but this association was attenuated when adjusted for body mass index (BMI) (OR = 1.290, 95% CI = 1.082 – 1.539, P = 0.004). Age at initiation of regular smoking was negatively related to CAD in patients with diabetes (OR = 0.187, 95% CI = 0.065 – 0.538, P = 0.002), but this association became insignificant when adjusted for education attainment (EA). Conclusions: This study supported the causal effect of smoking initiation and age at initiation of regular smoking on CAD risk in patients with diabetes. Additionally, this effect might be partially mediated by BMI and EA, respectively.